PEMANFAATAN AMPAS TEBU DALAM MENINGKATKAN PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) DI KOTA PALEMBANG DAN SUMBANGSIHNYA PADA MATA PELAJARAN BIOLOGI DI SMA - Yustina Hapida (Bioilmi: Jurnal Pendidikan, 2019)
Sugar cane organic waste including biomass waste which has a high lignocellulose content, good for mycelium growth so that it can be used as a medium for the growth of Jamur Tiram Putih (Pleurotus ostreatus). This study aims to determine the amount of ampas tebu can increase the growth of Jamur Tiram Putih (Pleurotus ostreatus). The results of the studied Observation After 24th day inoculated Jamur Tiram Putih (Pleurotus ostreatus), the addition of ampas tebu to the medium only affect the growth of mycelium . The dose of ampas tebu waste added to the medium are 150 gr, 250 gr, and 350 gr. At pH 6,5, temperatures range 22-25 oC, humidity 72 % and ampas tebu dose 350 gr can increased mycelium of Jamur Tiram Putih (Pleurotus ostreatus) growth.